Does Trade Policy Impact Food and Agriculture Global Value Chain Participation of Sub-Saharan African Countries? - Balié, Jean; Del Prete, Davide; Magrini, Emiliano; Montalbano, Pierluigi; Nenci, Silvia (Wiley, 2019)
The emergence of food and agriculture global value chains (GVCs) is challenging the way scholars look at trade data, as well as how policy makers establish their trade policies. The common perception is that Sub‐Saharan African (SSA) countries, unlike most Latin American and Asian countries, are not deeply integrated into global production networks. Consequently, it is believed that the border protection policies of the former may have a limited impact on GVC participation. This paper challenges this conventional knowledge in two ways. First, by decomposing bilateral gross export into its value added components, we show that the sectoral and bilateral SSA participation in GVC for food and agriculture is substantial. Second, we demonstrate that trade policies impact backward and forward value chain linkages. These results call for a refinement of trade policy priorities in SSA.